Income generation, guideline, SU Income Generating Guidelines for Souphanouvong University: https://doi.org/10.69692/SUJMRD1004102 - Misisouk, Sanh; Keoboualapheth, Soulideth; SIFONGXAY, Sangthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research is to analyze determinants of the guideline for income generation of Souphanouvong University, by distributing a questionnaire to 215 employees, using descriptive statistics and reference statistics, using a stepwise multiple regression model The results found that the guidelines to generate income from activities are based on the budget income provided by the state in combination with the creation of short-term courses, providing policies for students, improving teaching manuals, providing external academic services, expanding cooperation, transforming into a service and research center, renting space. On the one hand, to generate revenue in terms of management are creating incentives, putting in place the management rules that are oriented, having a person in charge, the revenue management task to have a single window, and providing a clear budget to be used in each period. Allow time for staff to provide services - generate income that is not too limited, each board should have a detailed plan to generate income, provide modern teaching and learning facilities, turn existing assets into capital, invest to improve the environment of the university more and more.